2014
DOI: 10.7314/apjcp.2014.15.6.2517
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Pre-mir-218 Polymorphism and Cancer Risk in the Chinese Population: a Meta-Analysis

Abstract: Background: Several recent studies have explored associations between pre-mir-218 polymorphism (rs11134527) and cancer risk. However, published data are still inconclusive. To obtain a more precise estimation of the relationship in the Chinese population, we carried out a meta-analysis for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…A meta-analysis showed that rs11134527 polymorphism was associated with risk of cervical cancer but not hepatocellular carcinoma [24] In the present study, no association was observed between rs11134527 and GC risk in all of the four genetic models (dominant model, recessive model, codominant model, and overdominant model). Jiang et al found that the G/G genotype of rs11134527 was significantly associated with a better prognosis of esophageal squamous cell carcinoma in a codominant model [25].…”
Section: Discussioncontrasting
confidence: 58%
“…A meta-analysis showed that rs11134527 polymorphism was associated with risk of cervical cancer but not hepatocellular carcinoma [24] In the present study, no association was observed between rs11134527 and GC risk in all of the four genetic models (dominant model, recessive model, codominant model, and overdominant model). Jiang et al found that the G/G genotype of rs11134527 was significantly associated with a better prognosis of esophageal squamous cell carcinoma in a codominant model [25].…”
Section: Discussioncontrasting
confidence: 58%
“…MiR-218 is a tumor suppressor gene that is expressed at significantly low levels in various tumors. Some targets of miR-218 , such as ROBO1, RICTOR, BIRC5 and LAMB3 , have been reported to participate in many cancer signaling pathways, such as the ERK/MAPK, Wnt/β-catenin , and Notch pathways [ 12 , 41 , 42 ]. These findings indicate that the up-regulation of miR-218 may reduce the risk of cancer by down-regulating these targets.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed the relationship between the miR-218 polymorphism and cancer risk in the Chinese population. Gao et al [ 12 ] reported a meta-analysis about cancer in the Chinese population, and their results revealed that the miR-218 rs11134527 A>G polymorphism is linked to a remarkable reduction in cancer risk in GG genotype people compared with AA and AG genotype people. Other studies have demonstrated that the miR-218 rs11134527 A>G polymorphism is related to the susceptibility to cervical cancer, esophageal squamous cell carcinoma, breast cancer, and neuroblastoma [ 13–16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs), the most common genetic variation, have been demonstrated to influence the expression or target site selection of miRNAs and thus are involved in a series of biological processes by interfering interaction between miRNAs and target mRNAs [8, 9]. SNPs present in the miRNA genes have been illustrated to be a potentially important mechanism in the development and progression of cancer [10, 11].…”
Section: Introductionmentioning
confidence: 99%